2017
DOI: 10.1371/journal.pone.0186605
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of different types of hair traps for brown bear research and monitoring

Abstract: Non-invasive sampling by hair-trapping is increasingly used worldwide in wildlife research. Despite this rise and the potential of hair samples for ecology and conservation studies, the relative performance of hair collection devices has been rarely tested. Here, we compare the effectiveness of five types of hair traps for brown bears Ursus arctos in the Carpathian Mountains (SE Poland) and test the effects of trap type, season, number of days elapsed since trap installation and trap features on the trapping s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…Male bears mark all year round but with a main peak during the mating season, a period of intense competition. This pattern has also been found at rubbing trees, both natural and artificially created to collect bear hairs (i.e., tree hair traps), in different ecosystems ( Green & Mattson, 2003 , Karamanlidis et al, 2010 ; Sato et al, 2014 ; Berezowska-Cnota et al, 2017 ; Lamb et al, 2017 ).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Male bears mark all year round but with a main peak during the mating season, a period of intense competition. This pattern has also been found at rubbing trees, both natural and artificially created to collect bear hairs (i.e., tree hair traps), in different ecosystems ( Green & Mattson, 2003 , Karamanlidis et al, 2010 ; Sato et al, 2014 ; Berezowska-Cnota et al, 2017 ; Lamb et al, 2017 ).…”
Section: Discussionmentioning
confidence: 60%
“…Bears choose specific trees in places that are well situated for the passage of other individuals ( Green & Mattson, 2003 ; Sato et al, 2014 ). At these sites there is an association between different communication behaviors, with marking behaviors triggering the subsequent sniffing and marking of later visitors ( Berezowska-Cnota et al, 2017 ). Nevertheless, these sites are not uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern has also been found at rubbing trees, both natural and artificially created to collect bear hairs (i.e. tree hair traps), in different ecosystems (Green & Mattson 2003, Karamanlidis et al 2010, Sato et al 2014, Berezowska-Cnota et al 2017, Lamb et al 2017.…”
Section: Why Brown Bears Visit These Sitesmentioning
confidence: 71%
“…It was recently shown that hair samples obtained from rubbing trees perform better for genotyping than hair samples collected by other noninvasive methods, such as hair from corral traps ( Berezowska-Cnota et al, 2017 ). We similarly observed that hair samples from rubbing trees performed best among the hair sample sources used in our study ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%